The effects of melatonin on the activity of the c-fos gene in the structures of the hypothalamic paraventricular nucleus under prolonged lighting - Bulyk, R. Y.; Abramov, A. V.; Bulyk, T. S.; Kryvchanska, M. I.; Vlasova, K. V.; Абрамов, Андрій Володимирович (My University, 2018)
The effect of constant illumination as a stress factor on the state of the "early response" c-fos gene in the lateral magnocellular subnuclei of the paraventricular nucleus (lmPVN) of the hypothalamus of rats at different time intervals (day and night) has been studied. To identify c-Fos in histological sections of the hypothalamus, a secondary (indirect) immunofluorescence method is used. Expression of the product of this gene, the c-Fos protein, in animals kept under normal conditions of alternation of illumination and darkness, shows a clear-cut circadian character. There was a significant decrease in the area of the immunopositive sites of structures at night by 19.4% compared to daytime measurements. The average values of the areas of such immunopositive subnuclei sites varied also in subgroups of rats under light stimulation conditions, in which samples of lmPVN were selected for study at 2 pm and 2 am, but the differences between groups did not reach the level of reliability. Under conditions of light stress, the c-Fos concentration index decreased by 29.4% during the day, and by 16.5% at night in relation to similar values in the intact group. In animals that were in the standard light mode, the c-Fos protein concentration index was significantly higher during the day than at night. In the intact group, the night value of the c-Fos concentration index averaged only 71.5% of the daily value. In rats subjected to constant illumination, the day and night values of the c-Fos concentration index did not differ reliably. To correct stress-induced changes in the activity of the "early response" c-fos gene in the rat hypothalamus, melatonin (0.5 mg/kg body weight of the animal) was used. Injections of melatonin to rats exposed to constant illumination normalized the circadian rhythm of the area of the material immunoreactive to c-Fos, compared to the group of animals that did not receive melatonin. When using melatonin against the background of constant illumination, a sharp increase of the protein concentration in the lmPVN subnuclei of hypothalamus in daytime and less pronounced at night intervals was detected. Injections of melatonin to animals were also reflected in the daily dynamics of the index of c-Fos protein content in the lmPVN subnuclei under conditions of constant illumination. In the daytime observation period, the index was almost twice the experimental data on stressed animals without the introduction of the hormone, bringing it closer to normal. Prospects for further research in this sphere will allow us to better understand the place and role of subnuclei of paraventricular nuclei of the hypothalamus in the mechanisms of the formation of circadian rhythms of the rat brain.
Keywords: lateral magnocellular subnuclei; gene expression; c-Fos protein; photoperiod